Computer algebra systems in the elementary number theory - Бедратюк, Леонід Петрович; Бедратюк, Ганна Іванівна (Eastern-European Journal of Enterprise Technologies, 2013)
Recently we have seen the active penetration of computer algebra systems to the educational process because it allows to form an innovative learning technologies. Almost every branch of mathematics the Maple developed the separate specialized package commands. However, currently these technologies, despite its effectiveness and visibility, for various reasons, are still not common in the classroom. The purpose of this article is to review basic information about the capabilities of computer algebra to solve some common problems of the elementary number theory, and which can be used to solve educational problems. The paper describes the package description commands NumberTheory of the computer algebra system Maple. The methods of solving some common problems in the number theory in Maple. Using discussed the team package Maple a teacher can illustrate the problem solving in the classroom for the subject of the elementary number theory.